(untitled) (Itinerarios Educativos, 2025)
This article reflects on the field of youth and adult education (Y&AE) from a gender perspective. Based on the narratives of students from an educational centre co–managed by a guild in Jujuy (Argentina), we investigate, on the one hand, how gender inequalities, specifically violence against women, affect educational experiences and generate obstacles to school continuity. On the other hand, it explores the impact of the liberating pedagogical action taken by the Educational Centre on women’s lives. The study uses biographical and participatory methodology and theoretical contributions from the socio–critical field of education. Among the main results, we can see that women highly value a kind of education that is politically and humanely attentive to their problems; consequently emphasizing the need to deepen the incorporation of the gender perspective in the educational culture and the Y&AE programmes in order to guarantee the right to education of women.